The Ukrainian war and Russophobia of the “Other Serbia” - Antonić, Slobodan (Napredak, 2023)
In the first part of the article, the theoretical framework of the analysis is given and the basic terms are explained. The second part presents examples of Russophobia in the texts of some members of the media and cultural elite in Serbia even before the outbreak of the war in Ukraine. The third part describes the escalation of Russophobia among that part of the elite after the Russian intervention in Ukraine (2022). The fourth part provides an overview of seven surveys of public opinion in Serbia (2022-2023). All these surveys show a high proportion of Serbian citizens (about 80%) who do not agree with the introduction of sanctions against Russia. An overview of attempts to ignore these findings by a part of the Russophobic elite in Serbia is also given. In the fifth part, the further escalation of Russophobia among the elite is described, and in the sixth part, an explanation of this phenomenon is presented from the perspective of the world system theory.